Factors influencing divestment decision‐making: Evidence from a field study - Duhaime, Irene M.; Grant, John H. (Strategic Management Journal, 1984)
Abstract This research investigates factors which influenced the corporate‐level divestment decisions of large, diversified firms. Field research, including interviews with corporate executives of 40 large diversified firms, provided the data to test propositions developed from various literature sources. In general, thefindings from this research indicate that a business unit's strength, its relationship to other units in its firm and its parent firm's financial position compared to its competitors are important divestment influences, whereas other factors such as general economic conditions are not. Some of the findings are consistent with conventional management wisdom, but others are counterintuitive.